PENERAPAN JOYFUL LEARNING DENGAN MEDIA POSTER MAGNETIK UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI PENINGGALAN SEJARAH KELAS V SD IT SALSABILA 5 PURWOREJO - Nur Asyifa, Laela; Putro Widoyoko, Sugeng Eko; Ngazizah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning interest of fifth-grade students at SD IT Salsabila 5 Purworejo in historical heritage material due to monotonous learning with minimal use of interactive media. This study aims to improve student learning interest through the application of Joyful Learning using magnetic poster media. This research employed a Classroom Action Research (CAR) design referring to the Kemmis and McTaggart model, conducted in two cycles involving 26 fifth-grade students. Data collection techniques used observation, tests, questionnaires, and interviews. Data analysis was performed using descriptive qualitative and quantitative methods. The implementation of Joyful Learning increased from 66.67% in cycle I to 88.89% in cycle II. Learning interest measured through observation also increased from 46.15% in the pre-cycle to 64.61% in cycle I and reached 86.92% in cycle II. The average learning interest questionnaire score increased from 43.81 in cycle I to 58.38 in cycle II, with an increase of 33.26%. Learning outcomes showed that the average posttest score increased from 75.19 to 83.00 with classical completeness of 84.61%. The N-Gain Score was 0.35 (moderate category). This increase concludes that the application of Joyful Learning with magnetic poster media can improve the learning interest of fifth-grade students at SD IT Salsabila 5 Purworejo.